MON-169 Characteristics of Patients with Recurrent EMS Utilization for Hypoglycemia in a Large Urban System - O'Connor, Mark (J Endocr Soc, 2019)
Background: Hypoglycemia is a life-threatening condition that frequently results in utilization of Emergency Medical Services (EMS). After prehospital treatment, many patients refuse to be transported to the hospital. Understanding the characteristics of hypoglycemic patients with high EMS utilization may help providers optimize resource allocation. Objective: To describe the demographics and clinical characteristics of patients who utilize EMS for hypoglycemia and to determine which factors are associated with recurrent EMS utilization. Methods: We performed a retrospective chart review of prehospital care records from the municipal EMS provider in a large city. All patients who received prehospital treatment for hypoglycemia (oral glucose, parenteral dextrose, or intramuscular glucagon) over a one-year period were identified. Patients with no recorded finger-stick glucose or an initial glucose level greater than 70 mg/dl were excluded, as were those in cardiac arrest and under 5 years of age. Extracted information included demographics, prehospital treatment, disposition, and the number of subsequent EMS utilizations within 365 days. We obtained median income data from the U.S. Census Bureau and the overall prevalence of diabetes in the city from the public health commission. Results: We identified 549 subjects, mean age 55 years (range 9 to 104, 65% male). The mean minimum glucose level was 44 mg/dl with standard deviation (SD) of 15. For treatment, 69% of patients received oral glucose, 26% received parenteral dextrose, 3% received glucagon, and 2% received more than one medication. At the index visit, 81% of patients accepted hospital transport and 19% refused. The rate of recurrent EMS utilization for hypoglycemia was 10%, and 3% of patients had three or more utilizations within the year. The mean blood glucose at the index visit was 38 mg/dl (SD 15) for patients with multiple EMS utilizations and 44 mg/dl (SD 14) in those with only one EMS visit (P=0.006). Repeat utilizers were more likely to have received medications other than oral glucose at the index visit, 51% versus 28% (P<0.001). Age, gender, median zip code income, and disposition were not associated with recurrent EMS utilization. The overall incidence of hypoglycemia requiring EMS treatment relative to the estimated diabetic population was 0.84% per year. Conclusion: A low proportion of patients utilizing EMS for hypoglycemia had subsequent EMS visits within 365 days. Those who did had lower blood glucose levels at the index visit and were more likely to receive prehospital treatment with medications other than oral glucose. Demographic characteristics were less useful at predicting repeat utilization. Refusing transport to the hospital after EMS treatment for hypoglycemia did not raise a patient's risk of recurrent utilization, suggesting that EMS treat-and-release protocols may be appropriate for some patients.